THE IMPACT OF ARTIFICIAL INTELLIGENCE AND BLOCKCHAIN TECHNOLOGIES ON CONTEMPORARY JURISPRUDENCE: LAW ENFORCEMENT AND REGULATORY FRAMEWORKS (Journal of actual problems of jurisprudence, 2026)
The article examines the impact of artificial intelligence and blockchain technologies on the development of contemporary jurisprudence in the Republic of Kazakhstan from the perspective of law enforcement practice and regulatory frameworks. It is shown that the use of these technologies affects not only the technical aspects of legal activity but also fundamental legal approaches. In particular, the methods of establishing legally significant facts, evidentiary requirements, the conduct of administrative procedures, as well as the practice of concluding and performing contracts are undergoing transformation. Based on an analysis of the current legislation of the Republic of Kazakhstan governing electronic documents, digital signatures, informatization, personal data protection, and administrative procedures, the key directions of legal adaptation to digital technologies are identified. The findings of the study may be applied in law enforcement practice and used in the further improvement of the legal regulation of digital technologies.This research was funded by the Science Committee of the Ministry of Science and Higher Education of the Republic of Kazakhstan (Grant No. AP 26199757 “Legal problems of transformation of Kazakhstan in the conditions of integration of artificial intelligence and blockchain technologies.”Keywords: artificial intelligence; blockchain; digital assets; electronic document; electronic digital signature; law enforcement; regulatory framework; administrative procedures; digital evidence; personal data; cybersecurity.